POLA KOMUNIKASI CAMAT DALAM PENINGKATAN KINERJA PEGAWAI (STUDI KASUS KECAMATAN ANGGERAJA KABUPATEN ENREKANG) - Kamaluddin Tajibu; Sintia Suherman (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2020)
This study is intended to determine the communication pattern of the sub-district head in improving employee performance in the Anggeraja District Office, Enrekang Regency. The topics of discussion include: 1) How is the communication pattern of the sub-district head in improving employee performance in the Office of the Anggeraja District, Enrekang Regency. 2) Supporting and inhibiting factors for the communication process between leaders and employees in improving employee performance in the Anggeraja District Office, Enrekang Regency.